The Influence of Service Quality, Transparency, and Religiosity on PT Bank Mandiri Employees' Interest in Donation to Ziswaf at The Mandiri Amal Insani Zakat (LAZ) Institution Medan Representative - Andira, Muhammad Fauzan; Ridwan, Muhammad (Bisei : Jurnal Bisnis dan Ekonomi Islam, 2025)
This study aims to analyze the influence of service quality, transparency, and religiosity on the interest of PT Bank Mandiri employees in distributing zakat, infaq, and waqf (ZISWAF) through the Medan Representative Office of the Mandiri Amal Insani Zakat Institution (LAZ MAI). This study used a quantitative descriptive approach with data collection through questionnaires to employees. The results showed that service quality did not have a significant influence on employee interest in distributing ZISWAF, while transparency and religiosity had a significant positive influence. This indicates that the institution's openness in managing funds and the individual's level of religiosity are the main factors that encourage employees to participate in Islamic philanthropic activities. In general, this study confirms that trust in zakat management institutions and the strength of personal spiritual values ​​play an important role in building interest in donating. Meanwhile, service quality tends to be considered a supporting factor that is not strong enough to influence donation decisions if it is not accompanied by high transparency and trust. These findings have important implications for the management of zakat institutions in the corporate environment. LAZ MAI Medan is advised to continue to maintain transparency in fund management and strengthen religious education activities to increase philanthropic awareness among employees.